Optimum Level of Dietary Crude Protein for Growth Performance and Carcass Characteristics of Finishing Pigs from 245 to 300 lb - J. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 238 pigs (DNA 600 × 241, initially 246.4 lb) were used in a 26-d trial to determine the optimum dietary CP concentration for growth performance and carcass characteristics of finishing pigs. Pens of 7 or 8 pigs were allotted by BW and randomly assigned to 1 of 5 dietary treatments with 6 replications per treatment. Dietary treatments included 5 levels of CP (9, 10, 11, 12, and 13%) that were formed by reducing the amount of feed-grade amino acids and increasing soybean meal in a corn-based diet. At d 26, pigs were transported to a packing plant for processing and carcass data collection. For overall growth performance, increasing CP improved (quadratic, P<0.05) ADG, F/G, and caloric efficiency with the greatest improvement as CP was increased from 9 to 11% with smaller, continued improvements as CP was further increased to 13%. For carcass characteristics, increasing CP increased (quadratic, P<0.05) carcass ADG and improved (quadratic, P<0.05) carcass feed efficiency and carcass caloric efficiency, with the greatest response for pigs fed the diet with 13% CP. Furthermore, increasing CP marginally increased (quadratic, P<0.10) HCW, with the greatest response for pigs fed the diet with 12% CP. In conclusion, ADG, F/G, caloric efficiency, carcass ADG, carcass feed efficiency, and carcass caloric efficiency were maximized in pigs fed diets with 13% CP. The greatest response for HCW was observed in pigs fed diets with 12% CP.
Keywords: amino acid; crude protein; finishing pigs